Rapid increase in non-vaccine serotypes causing invasive pneumococcal disease in England and Wales, 2000–17: a prospective national observational cohort study. Issue 4 (April 2018) - Ladhani, Shamez N; Collins, Sarah; Djennad, Abdelmajid; Sheppard, Carmen L; Borrow, Ray; Fry, Norman K; Andrews, Nicholas J; Miller, Elizabeth; Ramsay, Mary E
Summary: Background: Pneumococcal conjugate vaccines (PCVs) have substantially reduced the incidence of invasive pneumococcal disease caused by vaccine serotypes; however, replacement disease with non-PCV serotypes remains a concern. We describe the population effect of the seven-valent and 13-valent PCVs (PCV7 and PCV13) on invasive pneumococcal disease in England and Wales. Methods: Using national invasive pneumococcal disease surveillance data for 2016/17, we compared incidence rate ratios (IRRs) against pre-PCV13 (2008/09–2009/10) and pre-PCV7 (2000/01–2005/06) baselines. We also estimated the number of invasive pneumococcal disease cases prevented since the introduction of PCVs. Findings: In 2016/17, overall invasive pneumococcal disease incidence (9·87 cases per 100 000; 5450 cases) across all age groups was 37% lower (IRR 0·63, 95% CI 0·60–0·65) than pre-PCV7 incidence (14·79 per 100 000; 8167 cases) and 7% lower (0·93; 0·89–0·97) than pre-PCV13 incidence (10·13 per 100 000; 5595 cases). By 2016/17, PCV7-type invasive pneumococcal disease incidence across all age groups had decreased by 97% (0·24 per 100 000; 0·03, 0·02–0·04) compared with the pre-PCV7 period, whereas additional PCV13-type invasive pneumococcal disease decreased by 64% (1·66 per 100 000; 0·36, 0·32–0·40) since the introduction of PCV13. Invasive pneumococcal disease incidence due to non-PCV13 serotypes doubled (7·97 per 100 000; 1·97, 1·86–2·09) since the introduction of PCV7, and accelerated since 2013/14—especially serotypes 8, 12F, and 9N, which were responsible for more than 40% of invasive pneumococcal disease cases by 2016/17. Invasive pneumococcal disease incidence in children younger than 5 years remained stable since 2013/14, with nearly all replacement disease occurring in adults. We estimated 38 366 invasive pneumococcal disease cases were prevented in the 11 years since the introduction of PCV7. Interpretation: Both PCV7 and PCV13 have had a major effect in reducing the burden of invasive pneumococcal disease in England and Wales; however, rapid increases in some non-PCV13 serotypes are compromising the benefits of the programme. Funding: Public Health England.